Characterization of a Polyphenol Oxidase Having Monophenolase and Diphenolase Activities from a Wild Edible Mushroom, Russula delica - Keskin, S.; Saglam Ertunga, N.; Colak, A.; Yildirim Akatin, M.; Özel, A.; Kolcuoglu, Y. (Asian Journal of Chemistry, 2011)
A polyphenol oxidase (PPO) extracted from a wild edible mushroom, Russula delica, was characterized spectrophotometrically. Native polyacrylamide gel, stained with Ldihydroxyphenylalanine (L-DOPA), showed two bands supporting a polyphenol oxidase potential. pH and temperature optima were determined as 5.0 and 30 ºC, respectively, for both of 3- (4-hydroxyphenyl)-propionic acid (PHPPA) and 4-methylcatechol (4-MC). After incubating at this pH at 4 ºC for 24 h, the crude extract retained about 90 % of its original monophenolase and diphenolase activities. The crude extract conserved about 90 % of its activities after 1 h incubation at 30 ºC. Vmax and Km values were calculated as 769.2 U/mg protein and 0.92 mM, respectively, for monophenolase and 71.4 U/mg protein and 0.27 mM, respectively, for diphenolase activity. It was found that benzoic acid was a potent inhibitor for both activities and some metal ions affected the activities. It is clear that R. delica possess polyphenol oxidase activities having interesting properties.